Light works - Dillo, Sophia Dixon, author; Yust, Dave, 1939-, advisor; Faris, Suzanne, committee member; Kokoska, Mary-Ann, committee member; Lehene, Marius, committee member; McKee, Patrick L., committee member (Colorado State University. Libraries, 2009)
Light Works explores the incorporation of light into painting in both small wall works and large hanging installation works. The pieces have a quiet gentle presence that sets the tone of the space they inhabit. Light is incorporated into the pieces through the combination of opaque layers such as off-white paper and white paint, with transparent and translucent layers of plastic and Mylar. Varying combinations of these materials create subtle visual effects as the light interacts with the layers. Elements of shadow, light, and visual fogginess or clarity of material all occur depending on the viewer's spatial relationship to the works. These works are non-objective. They use all-over patterning in order to not establish a visual hierarchy between forms. The viewer's attention thus tends to alternate between the whole of the work and the particular forms of the pattern. The combination of scale, composition, light, color, material, and physical placement of the works creates a space of simplicity, openness, and stillness. The intention is to situate the viewer in the immediacy of direct experience. Instead of our usual mind of naming, comparison and association, these works try to evoke a felt sense that exists before labeling, before thinking. I intend to have this space invite a specific experience of beauty, beauty as an activity of mind, a mind that reaches out to an object and returns nourished.
Keywords: Art, Abstract; Painting, American -- 21st century